2014
DOI: 10.1111/dmcn.12550
|View full text |Cite
|
Sign up to set email alerts
|

Postural control at 4 years in very preterm children compared with term‐born peers

Abstract: COPCentre RESULTS VPT children had impaired static and dynamic balance, with increased postural sway under all conditions, and reduced flight times compared with children born at term. When results were adjusted for body weight, the only group differences in postural control were in the cognitive dual task (cm/s; mean difference 0.6; 95% confidence interval [CI] 0.02, 1.2; p=0.04) and flight times (ms; jumping; mean difference À26.0; 95% CI À47.1, À5.0; p=0.02; left leg hopping; mean difference À30.1; 95% CI À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
3
20
1
Order By: Relevance
“…The results showed that children born preterm achieved worse results in the tests compared to the control group. Another study consistent with the present one was documented by Lorefice et al [20]. It involved comparing 4-year-olds born prematurely and at term.…”
Section: Discussionsupporting
confidence: 88%
“…The results showed that children born preterm achieved worse results in the tests compared to the control group. Another study consistent with the present one was documented by Lorefice et al [20]. It involved comparing 4-year-olds born prematurely and at term.…”
Section: Discussionsupporting
confidence: 88%
“…Postural control depends on the integration of sensory, motor and cognitive systems [2], and deficits in postural control may result from impairments in any or all of these systems [3]. Deficits in postural control have been shown to contribute to activity limitations experienced by children with a wide range of conditions, for example: Cerebral Palsy [4], Developmental Coordination Disorder [5][6][7], Spina Bifida [8], Down syndrome [9], Autistic Spectrum Disorders [10], premature birth [11,12] and sensorineural hearing loss [13]. However, each of these studies has examined only certain sub-components of postural control due to the lack of a comprehensive clinical assessment for children.…”
Section: Introductionmentioning
confidence: 99%
“…One prior study has examined its use as an assessment tool in pediatrics, which demonstrated an ability to discriminate between four year old children who were born very pre-term and those born at term. 15 Despite this promising preliminary evidence, no studies have examined its utility in the acute injury setting, nor specifically examined the optimal balance assessment to perform in a pediatric population with concussion.…”
Section: Introductionmentioning
confidence: 99%